Rare‐Earth Permanent Magnet SmCo5 for Chiral Interfacial Spin‐Orbitronics. (12th August 2021) - Zhou, Heng‐An; Liu, Jiahao; Wang, Zidong; Zhang, Qihan; Xu, Teng; Dong, Yiqing; Zhao, Le; Je, Soong‐Geun; Im, Mi‐Young; Xu, Kun; Zhu, Jing; Jiang, Wanjun
Abstract: Interfacially asymmetric magnetic multilayers made of heavy metal/ferromagnet have attracted considerable attention in the spintronics community for accommodating spin‐orbit torques (SOTs) and meanwhile for hosting chiral spin textures. In these multilayers, the accompanied interfacial Dzyaloshinskii–Moriya interaction (iDMI) permits the formation of Néel‐type spin textures. While significant progresses have been made in Co, CoFeB, Co2 FeAl, CoFeGd based multilayers, it would be intriguing to identify new magnetic multilayers that could enable spin‐torque controllability and meanwhile host nanoscale skyrmions. In this report, first, thin films made of permanent magnet SmCo5 with perpendicular magnetic anisotropy are synthesized, in which the deterministic SOT switching, enabled by the spin Hall effect, in Pt/SmCo5 /Ta trilayer is demonstrated. Further, the stabilization of room‐temperature skyrmions with diameters ≈100 nm in [Pt/SmCo5 /Ta]15, together with a skyrmionium‐like spin texture in [Pt/SmCo5 /Ir]15 multilayers is shown. Based on the material specific parameters, micromagnetic simulations are also carried out. The results confirm the presence of chiral spin textures in this new material family. Through interfacial engineering, the results thus demonstrate that rare earth permanent magnets could be a new platform for studying interfacial chiral spintronics. Abstract : In rare‐earth permanent magnet SmCo5 based magnetic multilayers featuring perpendicular magnetic anisotropy, efficient spin‐orbit torque switching is demonstrated in the Pt/SmCo5 /Ta trilayer. Evidence of interfacial chiral magnetism, including isolated skyrmions and skyrmionium‐like spin texture in these multilayers is also revealed.